2013
DOI: 10.1007/s11033-012-2405-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase polymorphisms, asthma susceptibility and confounding variables: a meta-analysis

Abstract: Oxidative stress is one of the main risk factors for asthma development. Glutathione S-transferases play an important role in antioxidant defences and may influence asthma susceptibility. In particular, GSTM1 and GSTT1 positive/null genotypes and the GSTP1 Ile105 Val polymorphism have been analyzed in a number of genetic association studies, with conflicting outcomes. Two previous meta-analyses have attempted to clarify the associations between GST genes and asthma, but these studies have also showed contrasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…These potential confounding factors may interact with TLR polymorphisms to moderate asthma susceptibility. Genetic associations were shown to be significantly influenced by age75,76,77,78 likely because some genes are expressed in adults and not expressed in children and vice versa . Observational studies showed that the prevalence of asthma has increased during the last decade due to environmental factors 3.…”
Section: Discussionmentioning
confidence: 99%
“…These potential confounding factors may interact with TLR polymorphisms to moderate asthma susceptibility. Genetic associations were shown to be significantly influenced by age75,76,77,78 likely because some genes are expressed in adults and not expressed in children and vice versa . Observational studies showed that the prevalence of asthma has increased during the last decade due to environmental factors 3.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione S-transferases are a large family of proteins that participate in the metabolism of reactive oxygen species and detoxification of xenobiotics. Polymorphisms in the genes of glutathione S-transferase indicate an association between neonatal hyperbilirubinemia and allergy, asthma, and AD (27)(28)(29)(30). Bilirubin may increase intestinal protein permeability and may be associated with a higher risk of developing an allergy to cow milk protein in young infants (31).…”
Section: Articlesmentioning
confidence: 99%
“…The prevalence of atopic conditions also varies between ethnicities, though the causes of these differences are unclear [17]. There are studies suggesting there are associations between gene polymorphisms and the presence of atopic conditions [1820]. Thus, the associations between atopic conditions and different ethnicities may be biologically based.…”
Section: Introductionmentioning
confidence: 99%